Assessing Tourism Economic Impact on Local Community in Lenggong Valley - Mat Wahi, Anis Fadhilah; Yusop, Mohamad Azwan; Jaafar, Mastura; Othman, Abdul Ghapar (AENSI, 2015)
Later on its recognition received in 30th June 2012, Lenggong Valley should be given serious attention by local government in terms of it community development. Instead of just giving a brand to the site. The recognition as a World Heritage Site to any place is in the hope to increase the revenue and help to improve the income and quality of life of the people. Among the sectors that local people could venture into include transportation, food and beverages, lodging accommodation and tour operator. Quantitative method approach will be using to obtained data from the respondents. The survey form is distributed among four which are food and beverages, transportation,lodging accommodation and tour guide. Based on 119 respondents involved in business in the Lenggong Valley, this paper assess the economic impact on those sectors in Lenggong Valley after two years of it’s recognition.